1992
DOI: 10.1021/jm00089a006
|View full text |Cite
|
Sign up to set email alerts
|

A nonpromoting phorbol from the Samoan medicinal plant Homalanthus nutans inhibits cell killing by HIV-1

Abstract: Extracts of Homalanthus nutans, a plant used in Samoan herbal medicine, exhibited potent activity in an in vitro, tetrazolium-based assay which detects the inhibition of the cytopathic effects of human immunodeficiency virus (HIV-1). The active constituent was identified as prostratin, a relatively polar 12-deoxyphorbol ester. Noncytotoxic concentrations of prostratin from greater than or equal to 0.1 to greater than 25 microM protected T-lymphoblastoid CEM-SS and C-8166 cells from the killing effects of HIV-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
138
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(147 citation statements)
references
References 13 publications
8
138
1
Order By: Relevance
“…X-Gal (5-bromo-4-chloro-3-indolyl-␤-D-galactopyranoside) was also purchased from Sigma. Polymerase assays utilized the reagents poly(rAdT) [12][13][14][15][16][17][18] , poly(rC-dG) [12][13][14][15][16][17][18] , and poly(dT-dA) [12][13][14][15][16][17][18] (Pharmacia LKB, Piscataway, N.J.) and 16S-23S rRNA (Boehringer Mannheim, Indianapolis, Ind.) and random nonamer primers (Synthetic Genetics, San Diego, Calif.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…X-Gal (5-bromo-4-chloro-3-indolyl-␤-D-galactopyranoside) was also purchased from Sigma. Polymerase assays utilized the reagents poly(rAdT) [12][13][14][15][16][17][18] , poly(rC-dG) [12][13][14][15][16][17][18] , and poly(dT-dA) [12][13][14][15][16][17][18] (Pharmacia LKB, Piscataway, N.J.) and 16S-23S rRNA (Boehringer Mannheim, Indianapolis, Ind.) and random nonamer primers (Synthetic Genetics, San Diego, Calif.).…”
Section: Methodsmentioning
confidence: 99%
“…The preparation, enzymatic activities, and drug sensitivities of these two variant RTs have been previously described (5, 6). The three template-primer systems used to evaluate the inhibition of the various RT preparations by michellamine B consisted of poly(rA-dT) [12][13][14][15][16][17][18] , poly(rC-dG) [12][13][14][15][16][17][18] , and rRNA-primer. Recombinantderived DNA polymerases ␣ and ␤ were the kind gift of Sam Wilson (University of Texas Medical Branch, Center for Molecular Sciences).…”
Section: Effect Of Pretreatment Of Target Cells or Virus With Michellmentioning
confidence: 99%
“…Indeed, a number of compounds targeting protein kinase C are currently at different stages of drug development. Examples include LY333531, being evaluated for diabetic retinopathy and anti-angiogenesis (1, 2), prostratin and dPP, being evaluated for AIDS chemotherapy (3,4), and bryostatin 1 and ingenol 3-angelate, being evaluated as cancer chemotherapeutic agents (5)(6)(7).…”
mentioning
confidence: 99%
“…Because prostratin was structurally very close to a known tumor promoter, NCI considered stopping the research, but I argued that the contemporary ethnobotanical profile and the long history of use by the Samoan people indicated that it was not acutely toxic as were other phorbol esters. Based on these arguments, the NIH team continued in vivo studies with mice, and discovered that while prostratin activates protein kinase C, it does not promote tumors (Gustafson et al, 1992). Further field studies with Andrew Sorensen of the University of California, San Francisco medical school showed the disease "fiva samasama" (which I originally translated as "yellow fever" in my collection notes) was in fact hepatitis, raising the possibility that prostratin may serve to protect healthy cells from a range of viral pathogens.…”
Section: The Isolation Of Prostratin From a Samoan Medicinal Plantmentioning
confidence: 99%